2010
DOI: 10.1103/physrevlett.105.154503
|View full text |Cite
|
Sign up to set email alerts
|

Current-Voltage Characteristic of Electrospray Processes in Microfluidics

Abstract: We use a glass-based microfluidic device to study the electric current behavior of an electrospray process in the presence of a coflowing liquid. The current shows strong voltage dependence and weak flow rate dependence, in stark contrast to classical electrospray. By considering that the current is dominated by convection near the apex of the conical meniscus and driven by tangential electric stresses, we quantitatively capture the voltage and flow rate dependence of the current. Our results elucidate the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 39 publications
2
36
0
Order By: Relevance
“…They report a current that increases as the power 1/5 of the flow rate and the power 4/3 of the voltage, which they attribute to differences between the charge transport mechanisms in their jets and the jets of regular electrosprays in air (Fernández de la Mora 2007). Contrary to the viscous outer oil in the experiments of Gundabala et al (2010), the relatively inviscid hexane has little effect on the current transfer region in the experiments of Riboux et al, though the bath still affects the evolution of the whipping jet further downstream. Larriba & Fernández de la Mora (2010) obtained similar results for the current/flow rate and current/voltage characteristics of a cone-jet of an ionic liquid in a bath of heptane, and explained them as effects of the space charge due to the drops of the electrospray.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…They report a current that increases as the power 1/5 of the flow rate and the power 4/3 of the voltage, which they attribute to differences between the charge transport mechanisms in their jets and the jets of regular electrosprays in air (Fernández de la Mora 2007). Contrary to the viscous outer oil in the experiments of Gundabala et al (2010), the relatively inviscid hexane has little effect on the current transfer region in the experiments of Riboux et al, though the bath still affects the evolution of the whipping jet further downstream. Larriba & Fernández de la Mora (2010) obtained similar results for the current/flow rate and current/voltage characteristics of a cone-jet of an ionic liquid in a bath of heptane, and explained them as effects of the space charge due to the drops of the electrospray.…”
Section: Introductionmentioning
confidence: 84%
“…More recently, Gundabala, Vilanova & Fernández-Nieves (2010) set up an electrospray in a microfluidic device where a stream of very viscous conducting oil is surrounded by a co-flow of dielectric oil. They found that the current depends weakly on the flow rate and increases linearly with the applied voltage.…”
Section: Introductionmentioning
confidence: 99%
“…This effect has not been analyzed thoroughly, but it has several analogies with the regimes found independently by Gundabala et al 17 and by Larriba and de la Mora. 18 In the first case, Gundabala et al 17 integrated a submerged electrospray in a co-flow system, with relatively low surface tension (surfactantfree). They observed regimes in which the current almost does not depend on the flow rate but it depends strongly on the voltage applied.…”
Section: -11mentioning
confidence: 65%
“…The jet or droplet diameter can vary substantially depending mainly on the liquid conductivity, ranging from hundreds of micrometers for the least conducting liquids to a few nanometers for the most conducting ones. Finer control on the jet diameters can be achieved by manipulating the injected flow rate 16 or the voltage 17,18 depending on the regime in which the electrospray is manipulated. Additionally, the technique permits great flexibility in the applications, e.g., it also permits encapsulation of substances by the combination of two liquids into the so-called "coaxial-jet electrospray."…”
Section: -1058/2012/6(4)/044104/19/$3000mentioning
confidence: 99%
See 1 more Smart Citation